Mother’s Parenting Style and Television Media Access Determining Bullying Behavior on Elementary School Children - Rokoyah, Nurul Fitri Annisa; Hastuti, Dwi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
The purpose of this study was to analyze the influence of maternal parenting style and television media access on bullying behavior of elementary school children. The population in this study were 289 of 5th grade students in two sub-districts of Bogor with an age range of 10-12 years. The entire study sample consisted of 74 students selected using a simple random sampling technique. Data collection was using a questionnaire tool with self-report techniques and in-depth interviews as additional data. Data were processed and analyzed using multiple linear regression tests on the SPSS program. The results showed that less than half of mothers tend to have authoritative parenting styles. Children's access to television media is classified as the high category, which can be seen from the length of duration and the high frequency of watching television and the type of content that children watch is exposed to violence and not suitable to their age. Besides, bullying behavior that most children do is verbal bullying. The analysis results found that the mother's authoritarian parenting style and the high access of children using television media had a significant positive effect on the bullying behavior of elementary school children.